ChemInform Abstract: Highly Diastereoselective 1, 3‐Dipolar Cycloaddition via in situ Formed Ketimine Ylides. Issue 14 (20th March 2013) - Cheng, Yu; Liu, Ya‐Nan; Ye, Jia; He, Long; Kang, Tai‐Ran; Liu, Quan‐Zhong
Abstract Reaction of unsaturated keto esters with glycine derivative (II) is investigated with a view to obtaining the corresponding Michael adducts.